Cloud Point Extraction and Flame Atomic Absorption Spectrometric Determination of Lead and Cadmium in Natural Waters - TALEBI, S.M.; HABIB-OLLAHI, S.; SEMNANI, A. (Asian Journal of Chemistry, 2010)
A pre-concentration method for low concentrations of lead and cadmium in natural water using cloud point extraction is proposed. The analytes were complexed with O,Odiethyldithiophosphate and then Triton X-114 was added as a surfactant. The parameters affecting the pre-concentration efficiency were optimized. The proposed method was applied satisfactory for the determination of lead and cadmium concentrations in natural waters.